Photoelectrochemical Performance Dependence on Geometric Surface Area of Branched ZnO Nanowires. Issue 23 (7th October 2018) - Li, Xiaobing; Niu, Fujun; Su, Jinzhan; Guo, Liejin
Abstract: Nanoarray architectures beneficial for a large electrochemically active surface area, intense light adsorption, and fast charge transport have attracted increasing attention in the past few years as enhanced catalysts for photoelectrochemical water splitting. However, the correlation between architecture and optical/electrochemical properties are not fully understood yet. Here a hierarchically branched ZnO nanowire structure is used as an example to investigate the effect of its geometry on light absorption and electrochemically active surface area. We used a two‐step hydrothermal method to synthesize the ZnO branched nanowires grown on fluorine doped tin oxide (FTO) coated glasses. The branch size of the ZnO nanowires was adjusted by changing the hydrothermal parameters. The relationship between the geometric surface area and light absorption spectra as well as electrochemically active surface area were compared. It was found that with increase of geometric surface area the electrochemically active surface area increases monotonically but the light absorption first increased but then decreased. The monotone increase of the photoelectrochemical activity indicates that the large surface area facilitating the hole transfer reaction at the ZnO/electrolyte interface is profound to improve its photon‐to‐current conversion efficiency. Abstract : A hierarchically branched ZnO nanowire structure (B‐NW) deposited on fluorine‐doped tin oxide (FTO) coated glass is successfully synthesized by a two‐step hydrothermal method. The obtained B‐NW is used as a model structure to investigate the effect of its geometry on light absorption and electrochemically active surface area. Furthermore, B‐NWs are identified as promising geometry for light harvesting and photoelectrochemical applications.